Composite lithium metal negative electrode, preparation method thereof and lithium ion battery

By adopting a laminated structure of modified porous copper foil and lithium-containing metal foil in the negative electrode of the lithium metal battery, combined with the design of the electronic insulating layer and the solid electrolyte layer, the volume expansion and life problems of the negative electrode of the lithium metal battery during the charge and discharge cycle are solved. Achieve high first-time efficiency and long cycle life battery performance.

CN119170743APending Publication Date: 2024-12-20XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411236492.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The negative electrode of existing lithium metal batteries has a large volume expansion during the charge and discharge cycle, and its first effect and cycle life are relatively low.

Method used

Using two layers of modified porous copper foil and lithium-containing metal foil arranged in stacks, a new structure is formed to reduce lithium deposition by setting an electronic insulating layer on the modified porous copper foil and undergoing lithium-philic modification. Overpotential and volume changes to improve lithium deposition density and cycling performance.

Benefits of technology

It achieves high first-term efficiency and long cycle life of lithium metal negative electrode, reduces the contact between lithium and electrolyte, inhibits side reactions and interface deterioration and inactivation, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170743A_ABST
    Figure CN119170743A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode preparation, in particular to a composite lithium metal negative electrode and a preparation method thereof and a lithium ion battery, the composite lithium metal negative electrode comprises two layers of modified porous copper foils and a lithium-containing metal foil which are stacked, the lithium-containing metal foil is arranged between the two layers of modified porous copper foils, and the lithium-containing metal foil is arranged between the two layers of modified porous copper foils. An electronic insulating layer is arranged on one side, far away from the lithium-containing metal foil, of the modified porous copper foil, the modified porous copper foil is obtained by performing lithium-loving modification treatment on the porous copper foil with the electronic insulating layer arranged on one side, and a lithium-loving layer is formed on the surface of the porous copper foil with the electronic insulating layer arranged on one side through the lithium-loving modification treatment. According to the composite lithium metal negative electrode provided by the invention, the problems of relatively large volume expansion and short first efficiency and cycle life of the lithium metal negative electrode in charge and discharge cycles can be improved, so that the battery applying the composite lithium metal negative electrode has high first efficiency and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode preparation, and in particular to a composite lithium metal negative electrode and a preparation method thereof, and a lithium ion battery. Background Art

[0002] In high energy density battery systems, for the negative electrode, metallic lithium has an extremely high theoretical specific capacity (3860 mAh / g), the most negative reduction potential (-3.04 V, relative to the hydrogen standard potential) and an extremely small density (0.59 g / cm 3 ), so metallic lithium has a very attractive prospect in being used as a negative electrode for high-energy batteries.

[0003] At present, the more mature solution for the negative electrode used in high-energy-density lithium metal batteries (solid and liquid) is lithium-copper composite tape, that is, two lithium tapes with PET (polyethylene terephthalate) film on one side are combined with copper foil by physical rolling, and then the PET film is peeled off to obtain a lithium-copper composite tape with double-sided lithium metal, which is assembled into a full battery through cutting, lamination, welding and other processes. Another solution is to directly use a three-dimensional current collector as the negative electrode, such as foam copper, foam nickel, etc., so that lithium is directly deposited on the three-dimensional skeleton of the current collector when the battery is charged to inhibit the negative impact of volume expansion changes. In terms of full battery applications, the composite negative electrode prepared by lithium-copper composite tape has better first-effect and cycle performance, but due to the lack of host structure on the negative electrode side, the volume expansion of lithium metal deposition is large during the charge and discharge cycle, which makes the powdering serious, and finally leads to impedance increase and battery failure. Another solution is to directly use a three-dimensional current collector as the negative electrode. Although the volume expansion is not large, it will lead to continuous and large consumption of active lithium and electrolyte, resulting in low first-effect and cycle life.

[0004] Therefore, how to provide a composite lithium metal negative electrode to solve the problems of large volume expansion, low initial efficiency and cycle life in the charge and discharge cycle in the prior art is a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a composite lithium metal negative electrode and a preparation method thereof and a lithium ion battery. The composite lithium metal negative electrode provided by the present invention can improve the problems of large volume expansion, low first efficiency and cycle life of the lithium metal negative electrode during the charge and discharge cycle, so that the battery using the composite lithium metal negative electrode has high first efficiency and long cycle life.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a composite lithium metal negative electrode, comprising two stacked layers of modified porous copper foil and lithium-containing metal foil, wherein the lithium-containing metal foil is arranged between the two layers of the modified porous copper foil, an electronic insulating layer is arranged on a side of the modified porous copper foil away from the lithium-containing metal foil, and the modified porous copper foil is obtained by subjecting a porous copper foil having the electronic insulating layer arranged on a single side to a lithium-philic modification treatment, and the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil having the electronic insulating layer arranged on a single side.

[0008] The composite lithium metal negative electrode provided by the present invention can improve the problems of large volume expansion, low first efficiency and cycle life of the lithium metal negative electrode during the charge and discharge cycle, so that the battery using the composite lithium metal negative electrode has high first efficiency and long cycle life.

[0009] Further, the material of the electronic insulating layer includes PET;

[0010] And / or, the composite lithium metal negative electrode further comprises a solid electrolyte layer, the solid electrolyte layer is arranged on a side of the modified porous copper foil away from the lithium-containing metal foil, the solid electrolyte layer is also arranged on at least part of the pore wall of the modified porous copper foil, and at least part of the solid electrolyte layer can overflow through the pores of the modified porous copper foil onto the lithium-containing metal foil;

[0011] And / or, the modified porous copper foil is obtained by subjecting the pore walls of the porous copper foil with an electronic insulating layer on one side and the other side without the electronic insulating layer to lithium-philic modification;

[0012] And / or, the thickness of the electronic insulation layer is L2, and L2 is 3um-20um;

[0013] And / or, the thickness of the porous copper foil is L1, and L1 is 6um-15um;

[0014] And / or, the thickness of the porous copper foil with the electronic insulation layer on one side is L, and L is 15um-30um;

[0015] And / or, the diameter of the holes of the porous copper foil is R, and R is 30um-70um;

[0016] And / or, the center distance between two adjacent holes on the porous copper foil is D, and D is 70um-180um;

[0017] And / or, the length of the opening area on the porous copper foil is 80% to 100% of the length of the porous copper foil.

[0018] And / or, before the modified porous copper foil is compounded with the lithium-containing metal foil, in the width direction, the width of the porous copper foil is E, the opening area is located in the middle of the porous copper foil as a whole, the width of the opening area is E1, the width of the lithium-containing metal foil is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm;

[0019] And / or, the lithium-philic modification treatment includes at least one of in-situ chemical reaction generation, vapor deposition, and magnetron sputtering;

[0020] And / or, the material constituting the lithium-philic layer includes at least one of an oxide, a metal material, and a CNT;

[0021] And / or, the thickness of the lithium-containing metal foil is 5um-20um.

[0022] Further, the oxide includes at least one of ZnO, CuO, and Co3O4, and the metal material includes at least one of Au, Ag, Zn, Mg, and Al;

[0023] And / or, the in-situ chemical reaction generation comprises immersing the porous copper foil with the electronic insulating layer on one side thereof in a salt solution of a lithium-philic material for 0.5-3 hours, wherein the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L.

[0024] Furthermore, the material of the solid electrolyte layer includes a polymer electrolyte, an adhesive, an inorganic ceramic solid electrolyte and a lithium salt, wherein the polymer electrolyte includes at least one of PAN, Pvdf-HFP, PEO, PMMA, and PI, the adhesive includes at least one of PVDF, PAA, and CMC, the inorganic solid ceramic electrolyte includes at least one of LATP, LLZO, LLZTO, LGPS, LPSSiCl, LAGP, and LLTO, and the lithium salt includes at least one of LiTfsi, lifsi, LPF6, liPF4, and LiCLO4, and the mass ratio of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte, and the lithium salt is (15%-40%): (3%-10%: (40%-70%): (5%-15%), and the sum of the mass ratios of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte, and the lithium salt is 100%.

[0025] Furthermore, the polymer electrolyte includes Pvdf-HFP and PEO, the inorganic ceramic solid electrolyte includes LLZO, the adhesive includes PVDF, and the lithium salt includes LiTFSI. In terms of mass ratio, Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=(10%-40%):(3%-20%):(3%-10%):(20%-70%):(5%-10%).

[0026] In a second aspect, the present invention provides a method for preparing the composite lithium metal negative electrode as described in the first aspect, the preparation method comprising the following steps:

[0027] S1, providing two porous copper foils with an electronic insulating layer on one side, and performing lithium-philic modification treatment on the porous copper foil with an electronic insulating layer on one side to obtain two modified porous copper foils;

[0028] S2, placing the lithium-containing metal foil between two modified porous copper foils, with the electronic insulating layer on the modified porous copper foil away from the lithium-containing metal foil, and then rolling.

[0029] Furthermore, after step S2, the preparation method further comprises the following steps:

[0030] S3, dissolving and dispersing the polymer electrolyte, adhesive, inorganic ceramic solid electrolyte and lithium salt in an organic solvent to obtain a slurry of the solid electrolyte layer;

[0031] S4, using the material obtained in step S2 as a substrate, coating the slurry of the solid electrolyte layer on the material obtained in step S2, and obtaining the composite lithium metal negative electrode after drying;

[0032] And / or, in step S1, the thickness of the electronic insulation layer is L2, and L2 is 3um-20um;

[0033] And / or, in step S1, the thickness of the porous copper foil is L1, and L1 is 6um-15um;

[0034] And / or, in step S1, the thickness of the porous copper foil with the electronic insulation layer on one side is L, and L is 15um-30um;

[0035] And / or, in step S1, the diameter of the holes of the porous copper foil is R, and R is 30um-70um;

[0036] And / or, in step S1, the center distance between two adjacent holes on the porous copper foil is D, and D is 70um-180um;

[0037] And / or, in step S1, the length of the opening area on the porous copper foil is 80% to 100% of the length of the porous copper foil (13);

[0038] And / or, in step S1, before the modified porous copper foil is compounded with the lithium-containing metal foil, in the width direction, the width of the porous copper foil is E, the opening area is located in the middle of the porous copper foil as a whole, the width of the opening area is E1, the width of the lithium-containing metal foil is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm;

[0039] And / or, the lithium-philic modification treatment comprises immersing the porous copper foil with an electronic insulating layer on one side in a salt solution of a lithium-philic material for 0.5-3 hours, wherein the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L, and the salt solution of the lithium-philic material comprises a silver nitrate solution;

[0040] And / or, in step S2, the thickness of the lithium-containing metal foil is L3, and L3 is 5um-20um;

[0041] and / or, in step S2, the rolling is performed in a dry environment with a dew point less than -30°C, and during the rolling, the rollers are fed in the width direction and the front and back sides are rolled once each;

[0042] And / or, in step S2, the rolling includes: using a vertical roller machine to roll, adjusting the first roller gap distance to 30-50 microns, adjusting the pressure to 160-240 kg, and then rolling one side once with the width direction roller; then adjusting the second roller gap distance to be 2-5 microns smaller than the first roller gap distance, adjusting the pressure to 50-150 kg, and rolling the other side once with the width direction roller again.

[0043] Further, in step S3, the organic solvent includes at least one of acetonitrile and NMP, the solid content of the slurry is 20%-30%, and the slurry of the solid electrolyte layer is prepared in a dry environment with a dew point less than -30°C;

[0044] And / or, in step S3, the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt are dissolved and dispersed in an organic solvent, comprising: firstly mixing the adhesive, the lithium salt and the organic solvent, performing a first stirring dispersion under a vacuum degree of -80 to -90 kPa, and then adding the inorganic ceramic solid electrolyte for a second stirring dispersion to obtain a solution 1; adding the polymer electrolyte to the solution 1, performing a third stirring dispersion under a vacuum degree of -80 to -90 kPa, and finally performing vacuum defoaming to obtain a slurry of the solid electrolyte layer;

[0045] And / or, in step S4, the slurry of the solid electrolyte layer is coated on the material obtained in step S2, and the composite lithium metal negative electrode is obtained after drying, comprising: in a dry environment with a dew point less than -30°C, the slurry of the solid electrolyte layer is first coated on one side of the material obtained in step S2, and then vacuum-stood, after the slurry of the solid electrolyte layer is cast onto the pore wall of the modified porous copper foil and the surface of the lithium-containing metal foil, it is dried, and then the other side of the material obtained in step S2 is subjected to the same coating and drying treatment to obtain the composite lithium metal negative electrode;

[0046] and / or, in step S4, coating the slurry of the solid electrolyte layer on the material obtained in step S2 by wire rod coating, and then standing in vacuum for 5-20 minutes;

[0047] And / or, in step S4, the double-sided surface density of the slurry coating of the solid electrolyte layer is 28 to 36 g / m 2 ;

[0048] And / or, in step S4, the drying includes first performing vacuum drying at a vacuum degree of -80 to -90 kPa and a temperature of 50 to 70°C for 4 to 8 hours, and finally performing drying at a temperature of 30 to 50°C and normal pressure for 1 to 2 hours.

[0049] Further, in step S3, the stirring speed of the first stirring and dispersing is 15-25 r / min, the dispersing speed is 2500-3500 r / min, the temperature is room temperature, and the time is 0.5-2 h; the stirring speed of the second stirring and dispersing is 25-35 r / min, the dispersing speed is 4000-6000 r / min, the temperature is room temperature, and the time is 0.5-2 h; the third stirring and dispersing includes first stirring and dispersing at a stirring speed of 30-50 r / min and a dispersing speed of 900-1100 r / min at a temperature of 40-50° C. for 3-5 h, then turning off the heating, stirring and dispersing at a stirring speed of 10-30 r / min and a dispersing speed of 400-600 r / min, until naturally cooling to room temperature;

[0050] And / or, in step S3, the vacuum defoaming includes: setting stirring inversion, and performing vacuum defoaming at a stirring speed of 5 to 15 r / min and a dispersion speed of 0 r / min.

[0051] In a third aspect, the present invention provides a lithium-ion battery, which includes the composite lithium metal negative electrode described in the first aspect or the composite lithium metal negative electrode prepared by the preparation method described in the second aspect.

[0052] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0053] (1) The composite lithium metal negative electrode provided by the present invention can improve the problems of large volume expansion, low first efficiency and cycle life of the lithium metal negative electrode during the charge and discharge cycle, so that the battery using the composite lithium metal negative electrode has high first efficiency and long cycle life.

[0054] (2) The present invention adopts two porous copper foils with single-sided electronic insulating layers, and obtains modified porous copper foils by subjecting the copper foil pore walls and one side without the electronic insulating layer to lithium-philic modification. A lithium-containing metal foil is added between the two modified porous copper foils to obtain a new structure by rolling. The solid electrolyte layer is modified on the basis of the new structure. The lithium deposition overpotential is reduced through the lithium-philic sites. The electronic insulating layer shielding design of the non-perforated area allows lithium to be deposited on the pore walls and the interlayer metal lithium, which effectively slows down the charge and discharge volume change, improves the lithium deposition density, and improves the battery cycle performance. In addition, because the new structure only requires one layer of lithium-containing metal foil to be made Therefore, during composite rolling, there will be no problem of misalignment caused by inconsistent force and extension on both sides, which improves the cutting and assembly efficiency. At the same time, the lithium-containing metal foil is used as a lithium source to improve the initial efficiency. Through the design of the deposition position and the overall solid electrolyte layer, an ion channel is formed to uniformly flow ions. The growth of lithium dendrites is suppressed by its own mechanical strength, and the pore wall and the lithium-containing metal foil are protected by its own density and liquid absorption. The contact between the deposited lithium and the electrolyte is reduced, the side reaction is suppressed, and the volume expansion is further improved. The continuous consumption of active lithium and a series of interface deterioration, deactivation and safety problems caused by lithium dendrites are improved, thereby improving the battery cycle life as a whole. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0056] Figure 1 A schematic diagram of the structure of the modified porous copper foil provided by the present invention;

[0057] Figure 2 Another schematic diagram of the structure of the modified porous copper foil provided by the present invention;

[0058] Figure 3 A schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention;

[0059] Figure 4 Another schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention;

[0060] Figure 5Another schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention;

[0061] Figure 6 Another schematic diagram of another structure of the composite lithium metal negative electrode provided by the present invention.

[0062] Icons: 1-modified porous copper foil; 11-electronic insulation layer; 12-lithiophilic layer; 13-porous copper foil; 2-lithium-containing metal foil; 3-solid electrolyte layer. DETAILED DESCRIPTION

[0063] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0064] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0065] Figure 1 This is a schematic diagram of the structure of the modified porous copper foil provided by the present invention. Figure 2 Another schematic diagram of the structure of the modified porous copper foil provided by the present invention, Figure 3 This is a schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention, Figure 4 Another schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention is as follows: Figure 1 to Figure 4 As shown, in the first aspect, the present invention provides a composite lithium metal negative electrode, which comprises two stacked layers of modified porous copper foil 1 and lithium-containing metal foil 2, wherein the lithium-containing metal foil 2 is arranged between the two layers of the modified porous copper foil 1, and an electronic insulating layer 11 is arranged on a side of the modified porous copper foil 1 away from the lithium-containing metal foil 2, and the modified porous copper foil 1 is obtained by subjecting a porous copper foil 13 having the electronic insulating layer 11 arranged on a single side to a lithium-philic modification treatment, and the lithium-philic modification treatment forms a lithium-philic layer 12 on the surface of the porous copper foil 13 having the electronic insulating layer 11 arranged on a single side.

[0066] Specifically, the holes on the porous copper foil 13 are through holes.

[0067] The function of the electronic insulating layer 11 is to act as an ionic electronic insulator to prevent lithium from being deposited on the current collector outside the copper foil holes during charging, thereby preventing the volume from expanding too much.

[0068] The composite lithium metal negative electrode provided by the present invention can improve the problems of large volume expansion, low first efficiency and cycle life of the lithium metal negative electrode during the charge and discharge cycle, so that the battery using the composite lithium metal negative electrode has high first efficiency and long cycle life.

[0069] Any dense material that acts as an electronic insulator for the non-porous area on the porous copper foil 13 can be used as the material of the electronic insulating layer. In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the material of the electronic insulating layer 11 includes PET (polyethylene terephthalate).

[0070] Figure 5 Another schematic diagram of the structure of the composite lithium metal negative electrode provided by the present invention is shown in FIG. Figure 6 Another schematic diagram of another structure of the composite lithium metal negative electrode provided by the present invention, such as Figure 5 and Figure 6 As shown, in the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the composite lithium metal negative electrode also includes a solid electrolyte layer 3, and the solid electrolyte layer 3 is arranged on the side of the modified porous copper foil 1 away from the lithium-containing metal foil 2, and the solid electrolyte layer 3 is also arranged on at least part of the pore wall of the modified porous copper foil 1, and at least part of the solid electrolyte layer 3 can overflow through the pores of the modified porous copper foil 1 to the lithium-containing metal foil 2.

[0071] In the present invention, the solid electrolyte layer 3 can act as an ion conductor to conduct lithium ions, and at the same time, it can inhibit the growth of lithium dendrites by relying on its tough structure, thereby reducing the side reactions generated by the contact between the electrolyte and the deposited lithium.

[0072] The present invention adopts two porous copper foils 13 with single-sided electronic insulating layers 11 to obtain modified porous copper foils 1 by modifying the copper foil pore walls and one side 11 without the electronic insulating layer, and adds a lithium-containing metal foil 2 between the two modified porous copper foils 1 to obtain a new structure by rolling, so as to improve the assembly rate problem caused by appearance defects and reduce the lithium deposition nucleation overpotential; and based on the new structure, the solid electrolyte layer 3 is modified to obtain a composite lithium metal negative electrode, relying on the mechanical strength of the solid electrolyte layer 3 to improve volume expansion and inhibit lithium dendrites, relying on the density and liquid absorption of the solid electrolyte layer 3 to protect the pore walls and the lithium-containing metal foil 2, reducing the continuous consumption of active lithium, thereby improving a series of interface deterioration and deactivation and safety problems caused by volume expansion, continuous consumption of active lithium and lithium dendrites, and at the same time, the lithium-containing metal foil 2 is used as an excess lithium source to solve the problem of low first efficiency.

[0073] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the modified porous copper foil 1 is obtained by subjecting the pore wall of the porous copper foil 13 with the electronic insulating layer 11 on one side and the other side without the electronic insulating layer 11 to lithium-philic modification. The present invention introduces lithium-philic elements by subjecting the pore wall and the single side to lithium-philic modification, which can reduce the nucleation overpotential of the overall lithium during charge and discharge, induce lithium to preferentially deposit on the pore wall, improve the morphology of lithium deposition, reduce the longitudinal deposition amount of lithium, and reduce the deposition of lithium on the lithium-containing metal foil, thereby reducing volume expansion.

[0074] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the thickness of the electronic insulation layer 11 is L2, and L2 is 3um-20um, for example, L2 can be 3um, 5um, 10um, 15um or 20um.

[0075] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the thickness of the porous copper foil 13 is L1, and L1 is 6um-15um, for example, L1 can be 6um, 9um, 11um, 13um or 15um.

[0076] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the thickness of the porous copper foil 13 with the electronic insulating layer 11 on one side is L, and L is 15um-30um, for example, L can be 15um, 20um, 25um or 30um.

[0077] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the diameter of the hole of the porous copper foil 13 is R, R is 30um-70um, for example, R can be 30um, 35um, 40um, 45um, 50um, 55um, 60um, 65um or 70um. If the pore diameter is too large, the number of openings is small, the pore wall area is small, less lithium is deposited on the pore wall, and more lithium is deposited on the lithium-containing metal foil, and the volume expansion of the negative electrode is large during the charge and discharge cycle.

[0078] In order to ensure that the current collector (copper foil) structure next to the pore structure is not electrochemically corroded and melted by the charge and discharge cycle, losing the physical support of the overall structure and the electronic conductive network, in the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the center distance between two adjacent holes on the porous copper foil 13 is D, and D is 70um-180um, for example, D can be 70um, 90um, 110um, 130um, 150um, 170um or 180um.

[0079] In the above composite lithium metal negative electrode, as an optional embodiment, the length of the open area on the porous copper foil 13 is 80% to 100% of the length of the porous copper foil 13, for example, it can be 80%, 85%, 90%, 95% or 100%.

[0080] To ensure that when the modified porous copper foil 1 and the lithium-containing metal foil 2 are compositely rolled, the extension of the lithium-containing metal foil 2 in the width direction can cover the open area on the modified porous copper foil 1, and the excess extension does not affect the cutting and improve the assembly quality, in the above-mentioned composite lithium metal negative electrode, as an optional embodiment, before the modified porous copper foil 1 and the lithium-containing metal foil 2 are composited, in the width direction, the width of the porous copper foil 13 is E, the open area is located in the middle of the porous copper foil 13 as a whole, the width of the open area is E1, and the width of the lithium-containing metal foil 2 is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm (for example, E-E1 can be 20mm, 30mm, 40mm, 50mm or 60mm).

[0081] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the lithium-philic modification treatment includes at least one of in-situ chemical reaction generation, vapor deposition, and magnetron sputtering.

[0082] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the material constituting the lithium-philic layer 12 includes at least one of an oxide, a metal material, and a CNT (carbon nanotube). The specific process parameters for preparing the above-mentioned lithium-philic layer are not particularly limited, and those skilled in the art can design them according to specific circumstances.

[0083] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the oxide includes at least one of ZnO, CuO, and Co3O4, and the metal material includes at least one of Au, Ag, Zn, Mg, and Al.

[0084] Specifically, the pore wall and single-side modification treatment of the porous copper foil 13 is to introduce lithium-philic materials such as Au, Ag, Zn, Mg, Al, or some compounds such as ZnO, CuO, Co3O4, CNT, etc. at the interface through in-situ chemical reaction, vapor deposition, magnetron sputtering, etc.

[0085] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the in-situ chemical reaction generation includes immersing the porous copper foil 13 with the electronic insulating layer 11 on one side in a salt solution of a lithium-philic material for 0.5-3 hours (for example, 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours), and the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L.

[0086] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the thickness of the lithium-containing metal foil 2 is 5um-20um, for example, it can be 5um, 10um, 15um or 20um.

[0087] In the above-mentioned composite lithium metal negative electrode, as an optional implementation, the material of the solid electrolyte layer 3 includes a polymer electrolyte, a binder, an inorganic ceramic solid electrolyte and a lithium salt.

[0088] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the polymer electrolyte includes at least one of PAN (polyacrylonitrile), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), PEO (polyethylene oxide), PMMA (polymethyl methacrylate), and PI (polyimide), the binder includes at least one of PVDF (polyvinylidene fluoride), PAA (polyaryl acetylene), and CMC (carboxymethyl cellulose), and the inorganic solid ceramic electrolyte includes LATP, LLZO (Li7La3Zr2O 12 )、LLZTO(Li 6.4 LqCy 1.4 Ta 0.6 O 12 )、LGPS(Li 10 GeP2S 12 )、LPSSiCl(Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 )、LAGP(Li 1.5 Al 0.5 Ge 1.5 (PO4)3)、LLTO(Li 0.33 La 0.56The invention relates to a method for preparing a nanostructured carbon nanotube film comprising: preparing a nanostructured carbon nanotube film comprising at least one of LiTfsi (lithium tetrafluoroborate), Lifsi (lithium bis(fluorosulfonyl)imide salt), LPF6 (lithium hexafluorophosphate), LiPF4 (lithium tetrafluoro(malonic acid) phosphate), and LiCLO4 (lithium perchlorate). Preferably, the polymer electrolyte is PVdf-HFP (relative molecular weight 3 million) and PEO (relative molecular weight 500,000), the inorganic ceramic solid electrolyte is LLZO (particle sizes of 100 nm and 500 nm are mixed in a mass ratio of 1:1. According to this mixing ratio, the contact between the inorganic ceramic solid electrolytes will be better), the adhesive is PVDF, and the lithium salt is LiTFSI. Pvdf-HFP has a high dielectric constant and strong puncture strength after film formation. When combined with PEO, it will have better film uniformity, density and toughness. LLZO is a filler that increases the amorphous region of the polymer and promotes the dissociation of lithium salts to improve the ionic conductivity of the membrane. It connects with the space charge layer formed at the polymer interface to form a continuous high ionic conductivity percolation network, while increasing the mechanical strength of the membrane and inhibiting the wanton growth of lithium dendrites. According to the mass ratio, Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=(10%-40%) (for example, it can be 10%, 20%, 30% or 40%):(3%-20%) (for example, it can be 3%, 10%, 15% or 20%):(3%-10%):(20%-70%) (for example, it can be 20%, 30%, 40%, 50%, 60% or 70%):(5%-10%). If the PEO content is too low, the volume expansion will be large during the charge and discharge cycle.

[0089] In the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the mass ratio of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt is (15%-40%) (for example, it can be 15%, 20%, 30% or 40%): (3%-10%) (for example, it can be 3%, 5%, 7%, 10%): (40%-70%) (for example, it can be 40%, 50%, 60% or 70%): (5%-15%), and the sum of the mass ratios of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt is 100%.

[0090] In a second aspect, the present invention provides a method for preparing the composite lithium metal negative electrode as described in the first aspect, the preparation method comprising the following steps:

[0091] S1, providing two porous copper foils 13 with the electronic insulating layer 11 on one side, and performing lithium-philic modification treatment on the porous copper foil 13 with the electronic insulating layer 11 on one side to obtain two modified porous copper foils 1;

[0092] S2, placing the lithium-containing metal foil 2 between two modified porous copper foils 1, with the electronic insulating layer 11 on the modified porous copper foil 1 away from the lithium-containing metal foil 2, and then rolling.

[0093] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, after step S2, the preparation method further includes the following steps:

[0094] S3, dissolving and dispersing the polymer electrolyte, adhesive, inorganic ceramic solid electrolyte and lithium salt in an organic solvent to obtain a slurry of the solid electrolyte layer 3;

[0095] S4, using the material obtained in step S2 as a substrate, coating the slurry of the solid electrolyte layer 3 on the material obtained in step S2, and obtaining the composite lithium metal negative electrode after drying.

[0096] In the above-mentioned method for preparing the composite lithium metal negative electrode, as an optional implementation, in step S1, the thickness of the electronic insulating layer 11 is L2, and L2 is 3um-20um, for example, L2 can be 3um, 5um, 10um, 15um or 20um.

[0097] In the above-mentioned method for preparing the composite lithium metal negative electrode, as an optional implementation, in step S1, the thickness of the porous copper foil 13 is L1, and L1 is 6um-15um, for example, L1 can be 6um, 9um, 11um, 13um or 15um.

[0098] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, in step S1, the thickness of the porous copper foil 13 with the electronic insulating layer 11 on one side is L, and L is 15um-30um, for example, L can be 15um, 20um, 25um or 30um.

[0099] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional embodiment, in step S1, the diameter of the hole of the porous copper foil 13 is R, R is 30um-70um, for example, R can be 30um, 35um, 40um, 45um, 50um, 55um, 60um, 65um or 70um. If the pore diameter is too large, the number of openings is small, the pore wall area is small, less lithium is deposited on the pore wall, and more lithium is deposited on the lithium-containing metal foil 2, and the volume expansion of the negative electrode is large during the charge and discharge cycle.

[0100] In order to ensure that the current collector (copper foil) structure next to the pore structure is not electrochemically corroded and melted by the charge and discharge cycle, losing the physical support of the overall structure and the electronic conductive network, in the preparation method of the above-mentioned composite lithium metal negative electrode, as an optional implementation, in step S1, the center distance between two adjacent holes on the porous copper foil 13 is D, and D is 70um-180um, for example, D can be 70um, 90um, 110um, 130um, 150um, 170um or 180um.

[0101] In the above-mentioned method for preparing a composite lithium metal negative electrode, as an optional implementation, in step S1, the length of the open area on the porous copper foil 13 is 80% to 100% of the length of the porous copper foil 13, for example, it can be 80%, 85%, 90%, 95% or 100%.

[0102] In order to ensure that when the modified porous copper foil 1 and the lithium-containing metal foil 2 are compositely rolled, the extension of the lithium-containing metal foil 2 in the width direction can cover the open area on the modified porous copper foil 1, and the excess extension does not affect the cutting and improve the assembly quality, in the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, in step S1, before the modified porous copper foil 1 and the lithium-containing metal foil 2 are composited, in the width direction, the width of the porous copper foil 13 is E, the open area is located in the middle of the porous copper foil 13 as a whole, the width of the open area is E1, and the width of the lithium-containing metal foil 2 is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm (for example, E-E1 can be 20mm, 30mm, 40mm, 50mm or 60mm).

[0103] In the preparation method of the above-mentioned composite lithium metal negative electrode, as an optional embodiment, the lithium-philic modification treatment includes immersing the porous copper foil 13 with the electronic insulating layer 11 on one side in a salt solution of a lithium-philic material for 0.5-3 hours (for example, it can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours), the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L, and the salt solution of the lithium-philic material includes a silver nitrate solution. This embodiment uses a substitution reaction between a silver nitrate solution and copper to in situ generate an Ag-containing lithium-philic layer interface, and its purpose is to reduce the nucleation overpotential of the overall lithium during charge and discharge, induce lithium to preferentially deposit on the pore wall, improve the morphology of lithium deposition, and reduce the longitudinal deposition amount of lithium.

[0104] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, in step S2, the thickness of the lithium-containing metal foil 2 (before rolling) is L3, and L3 is 5um-20um, for example, 5um, 10um, 15um or 20um.

[0105] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, in step S2, the rolling is carried out in a dry environment with a dew point less than -30°C. During the rolling process, the roller is fed in the width direction and the front and back sides are rolled once each.

[0106] In the preparation method of the above-mentioned composite lithium metal negative electrode, as an optional embodiment, in step S2, the rolling includes: using a vertical roller machine for rolling, adjusting the first roller gap spacing to 30 to 50 microns (for example, it can be 30 microns, 35 microns, 40 microns, 45 microns or 50 microns), and adjusting the pressure to 160 to 240 kg (for example, it can be 160 kg, 180 kg, 200 kg, 220 kg or 240 kg), and then using the width direction to roll one side once; then adjusting the second roller gap spacing to 2-5 microns less than the first roller gap spacing, the pressure is adjusted to 50 to 150 kg (for example, it can be 50 kg, 100 kg or 150 kg), and again using the width direction to roll the other side once.

[0107] In the above-mentioned method for preparing a composite lithium metal negative electrode, as an optional embodiment, in step S3, the organic solvent includes at least one of acetonitrile and NMP (N-methyl-2-pyrrolidone), the solid content of the slurry is 20%-30% (for example, it can be 20%, 22%, 24%, 26%, 28% or 30%), and the slurry of the solid electrolyte layer is prepared in a dry environment with a dew point less than -30°C.

[0108] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional implementation, in step S3, the polymer electrolyte, adhesive, inorganic ceramic solid electrolyte and lithium salt are dissolved and dispersed in an organic solvent, including: first mixing the adhesive, lithium salt and the organic solvent, performing a first stirring and dispersing under a vacuum degree of -80 to -90 kPa, and then adding the inorganic ceramic solid electrolyte for a second stirring and dispersing to obtain solution 1; adding the polymer electrolyte to the solution 1, performing a third stirring and dispersing under a vacuum degree of -80 to -90 kPa, and finally performing vacuum defoaming to obtain a slurry of the solid electrolyte layer.

[0109] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional embodiment, in step S3, the stirring speed of the first stirring and dispersing is 15 to 25 r / min (for example, it can be 15 r / min, 20 r / min or 25 r / min), the dispersion speed is 2500 to 3500 r / min (for example, it can be 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 3000 r / min, 3200 r / min or 3500 r / min), the temperature is room temperature, and the time is 0.5 to 2h; the stirring speed of the second stirring and dispersing is 25 to 35 r / min (for example, it can be 25 r / min, 30 r / min or 35 r / min), the dispersion speed is 4000 to 6000 r / min (for example, it can be 4000 r / min, 4500 r / min, 5000 r / min, 5500 r / min or 60 00r / min), the temperature is room temperature, and the time is 0.5-2h; the third stirring and dispersing includes first stirring and dispersing at a stirring speed of 30-50r / min (for example, 30r / min, 40r / min or 50r / min), a dispersion speed of 900-1100r / min (for example, 900r / min, 1000r / min or 1100r / min) at a temperature of 40-50°C (for example, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C) for 3-5h, then turning off the heating, stirring and dispersing at a stirring speed of 10-30r / min (for example, 10r / min, 15r / min, 20r / min, 25r / min or 30r / min), a dispersion speed of 400-600r / min (for example, 400r / min, 500r / min or 600r / min), until naturally cooling to room temperature.

[0110] In the above-mentioned method for preparing a composite lithium metal negative electrode, as an optional implementation, in step S3, the vacuum defoaming includes: setting the stirring inversion, and performing vacuum defoaming at a stirring speed of 5 to 15 r / min (for example, 5 r / min, 10 r / min or 15 r / min) and a dispersion speed of 0 r / min.

[0111] In the above-mentioned method for preparing a composite lithium metal negative electrode, as an optional embodiment, in step S4, the slurry of the solid electrolyte layer 3 is coated on the material obtained in step S2, and the composite lithium metal negative electrode is obtained after drying, comprising: in a dry environment with a dew point less than -30°C, first coating the slurry of the solid electrolyte layer 3 on one side of the material obtained in step S2, and then standing in vacuum, after the slurry of the solid electrolyte layer 3 is cast onto the pore wall of the modified porous copper foil 1 and the surface of the lithium-containing metal foil 2, drying is performed, and then the other side of the material obtained in step S2 is subjected to the same coating and drying treatment to obtain the composite lithium metal negative electrode.

[0112] The embodiment of the present invention adopts a solution-casting method to form a film on the material obtained in step S2, dry it, and finally obtain a composite lithium metal negative electrode. The overall function of the solid electrolyte layer 3 is: the film formation on the surface makes it easier to assemble the negative electrode as a whole with the electrolyte or electrolyte membrane, diaphragm or positive electrode to form a better contact interface. At the same time, during the casting, the slurry will also penetrate into the holes and spread on the exposed lithium foil and pore wall. After the film is formed, an ion channel is formed to inhibit the growth of lithium dendrites, protect the pore wall and lithium-containing metal foil, reduce the contact degree between the deposited lithium and the electrolyte, and inhibit side reactions.

[0113] In the preparation method of the above-mentioned composite lithium metal negative electrode, as an optional implementation, in step S4, the slurry of the solid electrolyte layer 3 is coated on the material obtained in step S2 by wire rod coating using a 50μm wire rod, and then vacuum-standing for 5-20 minutes, for example, 5 minutes, 10 minutes, 15 minutes or 20 minutes.

[0114] In the above-mentioned preparation method of the composite lithium metal negative electrode, as an optional embodiment, in step S4, the double-sided surface density of the slurry coating of the solid electrolyte layer 3 is 28 to 36 g / m 2 , for example, it can be 28g / m 2 , 30g / m 2 , 32g / m 2 , 34g / m 2 or 36g / m 2 .

[0115] In the preparation method of the above-mentioned composite lithium metal negative electrode, as an optional embodiment, in step S4, the drying includes first vacuum drying for 4-8 hours under the conditions of a vacuum degree of -80 to -90 kPa and a temperature of 50 to 70°C (for example, 50°C, 55°C, 60°C, 65°C or 70°C), and finally drying for 1-2 hours at a temperature of 30 to 50°C (for example, 30°C, 35°C, 40°C, 45°C or 50°C) and normal pressure.

[0116] In a third aspect, the present invention provides a lithium-ion battery, which includes the composite lithium metal negative electrode described in the first aspect or the composite lithium metal negative electrode prepared by the preparation method described in the second aspect.

[0117] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0118] Example 1

[0119] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, and the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil. The solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil. A PET layer is arranged on the side of the modified porous copper foil away from the lithium foil. The modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment. The lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0120] The preparation method of the composite lithium metal negative electrode comprises the following steps:

[0121] S1. Soak two porous copper foils (thickness 10um, pore size R 30um, center distance D 80um) with a length of 2m, thickness 15um, width 200mm, opening area width 170mm, opening area length 2m, and a PET layer (thickness 5um) on one side that meets the specification parameter requirements in a 1mol / L silver nitrate solution for 1h. Then take out the copper foil and rinse it with deionized water first, then place it in an ultrasonic cleaning instrument filled with deionized water, adjust the frequency to 30KHz, and wash it twice, each time for 10 minutes, and finally place it in a blast oven at 60℃ to dry, so as to obtain a modified porous copper foil.

[0122] S2. Place a 2m long, 10um thick, 168mm wide lithium strip (lithium foil) in the middle between the two modified porous copper foils, i.e., in the center of the opening area, with the copper foil PET layer facing outward, and roll it with a vertical roller machine in a dry environment with a dew point less than -30°C. Adjust the roller gap to 39 microns, adjust the pressure to 200kg, and then use the width direction to roll one side once; then adjust the roller gap to 36 microns, adjust the pressure to 100kg, and use the width direction to roll again, and roll the other side once to obtain a new structure.

[0123] S3. Prepare the slurry of the solid electrolyte layer, using acetonitrile as the solvent, and the mass ratio of each component is: PVDF-HFP (relative molecular weight 3 million): PEO (relative molecular weight 500,000): PVDF: LLZO (particle size of 100nm and 500nm mixed in a mass ratio of 1:1): LiTFSI = 25%: 8%: 5%: 57%: 5%, and the overall slurry solid content is 25%. In order to ensure uniform distribution of each component, this scheme adopts a dissolution and dispersion method with constant temperature stirring at 45℃ in vacuum. The above operation needs to be carried out in a dry room with a dew point less than -30℃. The detailed steps are shown in S3-1 to S3-2 below:

[0124] S3-1: Take a certain amount of PVDF, LiTFSI and acetonitrile and add them to a stirring tank, open the vacuum, the vacuum degree is -90 kPa, set the stirring speed to 20 r / min, the dispersion speed to 3000 r / min, and disperse at room temperature for 1 hour; then add LLZO, open the vacuum, the vacuum degree is -90 kPa, set the stirring speed to 30 r / min, the dispersion speed to 5000 r / min, and disperse at room temperature for 1 hour to obtain solution 1;

[0125] S3-2: Add a certain mass of Pvdf-HFP and PEO to solution 1, set the stirring speed to 40r / min, the dispersion speed to 1000r / min, turn on the vacuum and heat to a constant temperature of 45 degrees Celsius, the vacuum degree is -90kPa, and the time is 4h. After the high-temperature dispersion is completed, turn off the heating, set the stirring speed to 20r / min, the dispersion speed to 500r / min until it cools naturally to room temperature, then set the stirring reverse speed to 10r / min, the dispersion speed to 0r / min, and vacuum defoam to obtain the slurry of the solid electrolyte layer.

[0126] S4. In a dry environment with a dew point less than -30°C, place the slurry of the solid electrolyte layer on the head of the new structure obtained in step S2, and apply it with a small automatic coating machine. Use 50um for the wire rod, and then vacuum (vacuum degree is -90kpa) and let it stand for 10 minutes, waiting for the slurry to be cast on the pore wall of the modified porous copper foil and the surface of the metal lithium, and then heat it to 60 degrees Celsius and vacuum (vacuum degree is -90kpa) to dry for 5h, and then take it out and place it in a blast oven at 40 degrees Celsius to dry for 1h. Then repeat the above operation on the other side of the new structure obtained in step S2 to obtain a composite lithium metal negative electrode, and the double-sided surface density of the coating is 30g / square meter. Cut the composite lithium metal negative electrode into small pieces according to size requirements.

[0127] The composite lithium metal negative electrode provided in this embodiment is used as the negative electrode, and the ternary material NCM811 is used as the positive electrode to assemble a full battery (lithium-ion battery). The specific assembly method includes the following steps:

[0128] A1: Prepare the positive electrode slurry with NCM811 positive electrode material, CNT, conductive carbon and PVDF in a mass ratio of 97:0.5:1:1.5 using solvent NMP according to the conventional process, and the double-sided surface density after drying is 35 mg / cm 2 Apply it on 12um aluminum foil, and then cut it into small pieces of corresponding size according to the battery design requirements;

[0129] A2: The diaphragms are all made of 8um PE-based diaphragms, which are stacked in a "Z" shape, with 10 layers of negative electrodes and 9 layers of positive electrodes. Then, the bare battery cell is obtained by hot pressing at 60 degrees Celsius and 0.2 tons of pressure for 30 seconds. Finally, the full battery cell is obtained by welding the tabs and encapsulating them with aluminum-plastic film, and injecting liquid. The total thickness of the battery cell is recorded as L4, the injection volume is 1.6g / Ah, and the electrolyte is an ester solution of 1mol / LLITFSI, in which the ester solvent is ethylene carbonate / fluoroethylene carbonate / dimethyl carbonate / ethyl methyl carbonate in a volume ratio of 1:1:1:1.

[0130] A soft-pack battery was prepared according to steps A1 and A2, with a theoretical capacity of 4AH and a thickness of L4=2.5mm.

[0131] Example 2

[0132] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil, the solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil, a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil, the modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment, the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0133] The preparation method of the composite lithium metal negative electrode is basically the same as that of Example 1, except that in step S3, the mass ratio of the components is: Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=30%:3%:5%:57%:5%.

[0134] In this example, the influence of the relative contents of Pvdf-HFP and PEO on the battery performance is investigated by changing the mass ratio of Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=25%:8%:5%:57%:5% in step S3 of Example 1 to Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=30%:3%:5%:57%:5%.

[0135] The lithium ion battery assembly method is the same as that in Example 1.

[0136] Example 3

[0137] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil, the solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil, a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil, the modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment, the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0138] The preparation method of the composite lithium metal negative electrode is basically the same as that of Example 1, except that in step S3, the mass ratio of each component is: Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=15%:8%:5%:67%:5%.

[0139] In this embodiment, the influence of the relative content of LLZO on the battery performance is investigated by changing the mass ratio of Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=25%:8%:5%:57%:5% in step S3 of embodiment 1 to Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=15%:8%:5%:67%:5%. The remaining steps are consistent with embodiment 1.

[0140] The lithium ion battery assembly method is the same as that in Example 1.

[0141] Example 4

[0142] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil and lithium foil stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, and a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil. The modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment. The lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0143] The preparation method of the composite lithium metal negative electrode is basically the same as that of Example 1, except that step S3 and step S4 are not included, and the new structure obtained in step S2 is directly cut into small pieces according to size requirements.

[0144] The lithium ion battery assembly method is the same as that in Example 1.

[0145] Example 5

[0146] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil, the solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil, a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil, the modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment, the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0147] The preparation method of the composite lithium metal negative electrode is basically the same as that of Example 1, except that in step S1, the diameter of the hole of the porous copper foil is R, R is 60um, and the center distance between two adjacent holes on the porous copper foil is D, D is 120um.

[0148] The lithium ion battery assembly method is the same as that in Example 1.

[0149] Example 6

[0150] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil, the solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil, a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil, the modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment, the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0151] The preparation method of the composite lithium metal negative electrode is substantially the same as that of Example 1, except that, in step S3, PEO is replaced by PI.

[0152] The lithium ion battery assembly method is the same as that in Example 1.

[0153] Example 7

[0154] The composite lithium metal negative electrode provided in this embodiment includes two layers of modified porous copper foil, lithium foil and solid electrolyte layer stacked together, wherein the lithium foil is arranged between the two layers of modified porous copper foil, the solid electrolyte layer is arranged on the side of the modified porous copper foil away from the lithium foil, the solid electrolyte layer is also arranged on the pore wall of the modified porous copper foil, the solid electrolyte layer can overflow onto the lithium foil through the pores of the modified porous copper foil, a PET layer is arranged on the side of the modified porous copper foil away from the lithium foil, the modified porous copper foil is obtained by subjecting the pore wall of the porous copper foil with the PET layer arranged on one side and the other side without the PET layer to lithium-philic modification treatment, the lithium-philic modification treatment forms a lithium-philic layer on the surface of the porous copper foil with the PET layer arranged on one side, and the material constituting the lithium-philic layer is silver.

[0155] The preparation method of the composite lithium metal negative electrode is substantially the same as that of Example 1, except that, in step S3, LLZO is replaced by LLTO.

[0156] The lithium ion battery assembly method is the same as that in Example 1.

[0157] Comparative Example 1

[0158] Take a lithium copper composite strip: the copper foil thickness is 10um, and the thickness of the lithium strips on both sides is 15um, cut it into small pieces that meet the stacking specifications, use the lithium copper composite strip as the negative electrode, and then assemble the battery according to the lithium ion battery assembly method in Example 1, with a thickness L4 = 2.45mm.

[0159] Comparative Example 2

[0160] The foam copper with a thickness of 40 μm was cut into small pieces that met the requirements of the stacking specifications, and the foam copper was used as the negative electrode. Then, the battery was assembled according to the lithium ion battery assembly method in Example 1, and the thickness L4 was 2.45 mm.

[0161] Comparative Example 3

[0162] The composite lithium metal negative electrode provided in this comparative example is substantially the same as that in Example 1, except that no PET layer is provided on the porous copper foil.

[0163] The composite lithium metal negative electrode was prepared by referring to the preparation method of Example 1.

[0164] The lithium ion battery assembly method is the same as that in Example 1.

[0165] Performance Testing

[0166] The thickness and cycle performance of the lithium-ion batteries provided in the embodiments and comparative examples were tested using a dilatometer, the mode was a constant pressure mode, and the pressure was uniformly 150kg. The first cycle charge and discharge test was carried out at a charge and discharge rate of 0.33C / 0.33C at room temperature 25°C, and the cut-off voltage was 2.8V~4.3V. The subsequent cycle test charge and discharge rate was 0.5C / 0.5C, and the cut-off voltage was 2.8V~4.3V. Among them, the expansion rate 1 = (first cycle full charge thickness - initial thickness) / initial thickness; expansion rate 2 = (10th cycle full discharge thickness - first cycle full discharge thickness) / first cycle full discharge thickness, first efficiency = first discharge capacity / first charge capacity, 10th cycle coulomb efficiency = 10th cycle discharge capacity / 10th cycle charge capacity.

[0167] The battery test data of the above embodiments and comparative examples are shown in Table 1.

[0168] Table 1

[0169]

[0170]

[0171] From Table 1 we can at least see that:

[0172] (1) Comparing the results of Example 1 and Example 2, the difference is that the content of PEO in Example 2 is less: it is found that the discharge capacity and first efficiency of Example 2 are slightly higher than those of Example 1, which indicates that the low ion conductivity of PEO will increase polarization and affect the capacity; the expansion rate 2 after 10 cycles is twice that of Example 1, which indicates that the PEO content has an inhibitory effect on negative electrode protection and reducing the accumulation of dead lithium caused by side reactions.

[0173] (2) Comparing the results of Example 1 and Example 3, the cycle life of Example 3 is longer, which indicates that the increase in the content of inorganic components is more conducive to the dense deposition of lithium.

[0174] (3) Comparing the results of Example 1 and Example 4, it is found that Example 4 has a larger volume expansion (larger expansion rate 1), more dead lithium accumulation (larger expansion rate 2), and worse cycle performance. This shows that the presence of the solid electrolyte layer can better improve the electrochemical performance of the battery as a whole. The reason may be that the solid electrolyte layer can act as an ion conductor to conduct lithium ions, and at the same time, it can inhibit the growth of lithium dendrites and improve volume expansion by relying on its tough structure. It relies on the density and liquid absorption of the solid electrolyte layer to protect the pore wall and lithium-containing metal foil, reduce the continuous consumption of active lithium, thereby improving a series of interface deterioration and deactivation and safety problems caused by volume expansion, continuous consumption of active lithium, and lithium dendrites, reducing the accumulation of dead lithium at the interface, and improving the cycle performance of the battery.

[0175] (4) Comparing the results of Example 5 with those of Example 1, the difference is that the pore diameter and the pore spacing are larger than those of Example 1: It is found that the first full circle thickness of Example 5 increases by 0.4%, indicating that the deposition sites of lithium on the pore wall are reduced, which will increase the amount of lithium deposited on the lithium foil when the battery cell is charged, causing the overall expansion of the battery cell to increase. It is also found that the tenth full circle thickness of Example 5 increases and the cycle life decreases, indicating that the increase in pore diameter and pore spacing will lead to an increase in the average current density of the negative electrode and an increase in the amount of dead lithium, which is not conducive to the performance of the battery cell.

[0176] (5) Compared with Example 1, Example 6 shows a serious deterioration in cycle life, with the full discharge thickness increasing and the coulombic efficiency decreasing in the tenth cycle, indicating that PI is unstable on the negative electrode side and continuously reacts with the electrolyte or metallic lithium, resulting in poor thermal stability on the negative electrode side.

[0177] (6) Compared with Example 1, Example 7 has the same problem as Example 6. The reason is that the tetravalent Ti ions in LLTO will be continuously reduced and degraded with lithium metal, and finally generate Ti, which will increase the electronic conductivity and decrease the ionic conductivity. At the same time, Ti metal will also catalyze the decomposition of the polymer PEO, so that the coulomb efficiency and cycle performance of the 10th cycle will be significantly reduced.

[0178] (7) Comparison of the results of Example 4 and Comparative Example 1 shows that the cycle life is improved, the expansion rate 1 is significantly reduced, indicating that the volume expansion is greatly improved, and the expansion rate 2 is significantly reduced, indicating that the amount of dead lithium accumulation is reduced. The composite negative electrode prepared by the lithium-copper composite tape in Comparative Example 1 has the following problems: in terms of appearance, due to the strong ductility and creep of lithium, some places are unevenly stressed and copper is easily exposed, and the lithium tapes on both sides have different ductility, which makes it impossible to align the lithium coverage areas on both sides in the width direction, affecting the efficiency of subsequent cutting and assembly; in terms of full battery application, the volume expansion of lithium metal deposition is large during the cycle due to the lack of a host structure on the negative electrode side; at the same time, the uneven deposition of lithium on the negative electrode side is easy to form lithium dendrites, which poses a safety risk of piercing the diaphragm and short-circuiting the positive electrode. During discharge, the dendrites melt and become inactivated from the root, and accumulate into dead lithium and form holes at the interface, which further deteriorates the contact interface of the electrolyte, seriously affecting the transmission of electrons and ions, thereby affecting the cycle life of the battery.

[0179] (8) Compared with Example 2, the first effect and cycle life of Example 4 are greatly improved.

[0180] (9) Compared with Example 1, the thickness of the first full charge cycle and the thickness of the tenth full discharge cycle of Comparative Example 3 are significantly increased, and the cycle life is greatly reduced, indicating that the PET electronic insulation layer is more conducive to the deposition of lithium ions on the pore wall and the main lithium belt, thereby reducing expansion and dead lithium accumulation, thereby improving the cycle life.

[0181] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite lithium metal negative electrode, characterized in that The composite lithium metal negative electrode comprises two layers of modified porous copper foil (1) and lithium-containing metal foil (2) which are stacked, wherein the lithium-containing metal foil (2) is arranged between the two layers of the modified porous copper foil (1), an electronic insulating layer (11) is arranged on one side of the modified porous copper foil (1) away from the lithium-containing metal foil (2), and the modified porous copper foil (1) is obtained by subjecting a porous copper foil (13) having the electronic insulating layer (11) arranged on one side to a lithium-philic modification treatment, wherein the lithium-philic modification treatment forms a lithium-philic layer (12) on the surface of the porous copper foil (13) having the electronic insulating layer (11) arranged on one side.

2. The composite lithium metal negative electrode according to claim 1, characterized in that The material of the electronic insulating layer (11) includes PET; And / or, the composite lithium metal negative electrode further comprises a solid electrolyte layer (3), the solid electrolyte layer (3) being arranged on a side of the modified porous copper foil (1) away from the lithium-containing metal foil (2), the solid electrolyte layer (3) being also arranged on at least a portion of the pore walls of the modified porous copper foil (1), and at least a portion of the solid electrolyte layer (3) being able to overflow through the pores of the modified porous copper foil (1) onto the lithium-containing metal foil (2); And / or, the modified porous copper foil (1) is obtained by subjecting the pore walls of a porous copper foil (13) provided with an electronic insulating layer (11) on one side and the other side not provided with the electronic insulating layer (11) to lithium-philic modification treatment; And / or, the thickness of the electronic insulating layer (11) is L2, and L2 is 3um-20um; And / or, the thickness of the porous copper foil (13) is L1, and L1 is 6um-15um; And / or, the thickness of the porous copper foil (13) with the electronic insulating layer (11) disposed on one side is L, and L is 15 um-30 um; And / or, the diameter of the holes of the porous copper foil (13) is R, and R is 30um-70um; And / or, the center distance between two adjacent holes on the porous copper foil (13) is D, and D is 70um-180um; And / or, the length of the opening area on the porous copper foil (13) is 80% to 100% of the length of the porous copper foil (13); And / or, before the modified porous copper foil (1) and the lithium-containing metal foil (2) are compounded, in the width direction, the width of the porous copper foil (13) is E, the opening area is located in the middle of the porous copper foil (13) as a whole, the width of the opening area is E1, the width of the lithium-containing metal foil (2) is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm; And / or, the lithium-philic modification treatment includes at least one of in-situ chemical reaction generation, vapor deposition, and magnetron sputtering; And / or, the material constituting the lithium-philic layer (12) includes at least one of an oxide, a metal material, and a CNT; And / or, the thickness of the lithium-containing metal foil (2) is 5um-20um.

3. The composite lithium metal negative electrode according to claim 2, characterized in that The oxide includes at least one of ZnO, CuO, and Co3O4, and the metal material includes at least one of Au, Ag, Zn, Mg, and Al; And / or, the in-situ chemical reaction generation comprises immersing the porous copper foil (13) having the electronic insulating layer (11) disposed on one side thereof in a salt solution of a lithium-philic material for 0.5-3 hours, wherein the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L.

4. The composite lithium metal negative electrode according to claim 2, characterized in that The material of the solid electrolyte layer (3) comprises a polymer electrolyte, an adhesive, an inorganic ceramic solid electrolyte and a lithium salt, wherein the polymer electrolyte comprises at least one of PAN, Pvdf-HFP, PEO, PMMA and PI, the adhesive comprises at least one of PVDF, PAA and CMC, the inorganic solid ceramic electrolyte comprises at least one of LATP, LLZO, LLZTO, LGPS, LPSSiCl, LAGP and LLTO, the lithium salt comprises at least one of LiTfsi, lifsi, LPF6, liPF4 and LiCLO4, the mass ratio of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt is (15%-40%): (3%-10%): (40%-70%): (5%-15%), and the sum of the mass ratios of the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt is 100%.

5. The composite lithium metal negative electrode according to claim 4, characterized in that The polymer electrolyte includes Pvdf-HFP and PEO, the inorganic ceramic solid electrolyte includes LLZO, the adhesive includes PVDF, and the lithium salt includes LiTFSI. In terms of mass ratio, Pvdf-HFP:PEO:PVDF:LLZO:LiTFSI=(10%-40%):(3%-20%):(3%-10%):(20%-70%):(5%-10%).

6. A method for preparing a composite lithium metal negative electrode as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1, providing two porous copper foils (13) with an electronic insulating layer (11) disposed on one side, and performing lithium-philic modification treatment on the porous copper foil (13) with an electronic insulating layer (11) disposed on one side to obtain two modified porous copper foils (1); S2. Placing the lithium-containing metal foil (2) between two modified porous copper foils (1), with the electronic insulating layer (11) on the modified porous copper foil (1) away from the lithium-containing metal foil (2), and then rolling.

7. The method for preparing a composite lithium metal negative electrode according to claim 6, characterized in that: After step S2, the preparation method further comprises the following steps: S3, dissolving and dispersing the polymer electrolyte, adhesive, inorganic ceramic solid electrolyte and lithium salt in an organic solvent to obtain a slurry of the solid electrolyte layer (3); S4, using the material obtained in step S2 as a substrate, coating the slurry of the solid electrolyte layer (3) on the material obtained in step S2, and obtaining the composite lithium metal negative electrode after drying; And / or, in step S1, the thickness of the electronic insulating layer (11) is L2, and L2 is 3um-20um; And / or, in step S1, the thickness of the porous copper foil (13) is L1, and L1 is 6um-15um; And / or, in step S1, the thickness of the porous copper foil (13) provided with the electronic insulating layer (11) on one side is L, and L is 15um-30um; And / or, in step S1, the diameter of the holes of the porous copper foil (13) is R, and R is 30um-70um; And / or, in step S1, the center distance between two adjacent holes on the porous copper foil (13) is D, and D is 70um-180um; And / or, in step S1, the length of the opening area on the porous copper foil (13) is 80% to 100% of the length of the porous copper foil (13); And / or, in step S1, before the modified porous copper foil (1) and the lithium-containing metal foil (2) are compounded, in the width direction, the width of the porous copper foil (13) is E, the opening area is located in the middle of the porous copper foil (13) as a whole, the width of the opening area is E1, the width of the lithium-containing metal foil (2) is E2, and each width satisfies: 2mm≤E1-E2≤4mm, 20mm≤E-E1≤60mm; And / or, the lithium-philic modification treatment comprises immersing the porous copper foil (13) having the electronic insulating layer (11) on one side thereof in a salt solution of a lithium-philic material for 0.5-3 hours, wherein the concentration of the salt solution of the lithium-philic material is 0.5-2 mol / L, and the salt solution of the lithium-philic material comprises a silver nitrate solution; And / or, in step S2, the thickness of the lithium-containing metal foil (2) is L3, and L3 is 5um-20um; and / or, in step S2, the rolling is performed in a dry environment with a dew point less than -30°C, and during the rolling, the rollers are fed in the width direction and the front and back sides are rolled once each; And / or, in step S2, the rolling includes: using a vertical roller machine to roll, adjusting the first roller gap distance to 30-50 microns, adjusting the pressure to 160-240 kg, and then rolling one side once with the width direction roller; then adjusting the second roller gap distance to be 2-5 microns smaller than the first roller gap distance, adjusting the pressure to 50-150 kg, and rolling the other side once with the width direction roller again.

8. The method for preparing a composite lithium metal negative electrode according to claim 7, characterized in that: In step S3, the organic solvent comprises at least one of acetonitrile and NMP, the solid content of the slurry is 20%-30%, and the slurry of the solid electrolyte layer (3) is prepared in a dry environment with a dew point less than -30°C; And / or, in step S3, the polymer electrolyte, the adhesive, the inorganic ceramic solid electrolyte and the lithium salt are dissolved and dispersed in an organic solvent, comprising: firstly mixing the adhesive, the lithium salt and the organic solvent, performing a first stirring dispersion under a vacuum degree of -80 to -90 kPa, then adding the inorganic ceramic solid electrolyte for a second stirring dispersion to obtain a solution 1; adding the polymer electrolyte to the solution 1, performing a third stirring dispersion under a vacuum degree of -80 to -90 kPa, and finally performing vacuum defoaming to obtain a slurry of the solid electrolyte layer (3); And / or, in step S4, the slurry of the solid electrolyte layer (3) is coated on the material obtained in step S2, and the composite lithium metal negative electrode is obtained after drying, comprising: in a dry environment with a dew point less than -30°C, the slurry of the solid electrolyte layer (3) is first coated on one side of the material obtained in step S2, and then vacuum-stirred, after the slurry of the solid electrolyte layer (3) is cast onto the pore wall of the modified porous copper foil (1) and the surface of the lithium-containing metal foil (2), drying is performed, and then the other side of the material obtained in step S2 is subjected to the same coating and drying treatment to obtain the composite lithium metal negative electrode; and / or, in step S4, coating the slurry of the solid electrolyte layer (3) on the material obtained in step S2 by wire rod coating, and then standing in vacuum for 5-20 minutes; And / or, in step S4, the double-sided surface density of the slurry coating of the solid electrolyte layer (3) is 28 to 36 g / m 2 ; And / or, in step S4, the drying includes first performing vacuum drying at a vacuum degree of -80 to -90 kPa and a temperature of 50 to 70°C for 4 to 8 hours, and finally performing drying at a temperature of 30 to 50°C and normal pressure for 1 to 2 hours.

9. The method for preparing a composite lithium metal negative electrode according to claim 8, characterized in that: In step S3, the stirring speed of the first stirring and dispersing is 15-25 r / min, the dispersing speed is 2500-3500 r / min, the temperature is room temperature, and the time is 0.5-2 h; the stirring speed of the second stirring and dispersing is 25-35 r / min, the dispersing speed is 4000-6000 r / min, the temperature is room temperature, and the time is 0.5-2 h; the third stirring and dispersing includes first stirring and dispersing at a stirring speed of 30-50 r / min and a dispersing speed of 900-1100 r / min at a temperature of 40-50° C. for 3-5 h, then turning off the heating, stirring and dispersing at a stirring speed of 10-30 r / min and a dispersing speed of 400-600 r / min, until naturally cooling to room temperature; And / or, in step S3, the vacuum defoaming includes: setting stirring inversion, and performing vacuum defoaming at a stirring speed of 5 to 15 r / min and a dispersion speed of 0 r / min.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the composite lithium metal negative electrode according to any one of claims 1 to 5 or the composite lithium metal negative electrode prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Porous collector and preparation method and lithium battery thereof

    CN108550859A

  • Three-dimensional structure composite metal lithium negative electrode and preparation method thereof

    CN111613772A

  • Composite lithium metal negative electrode and preparation method thereof

    CN112768637A

  • Current collector modification method, and modified current collector and application thereof

    CN113036071A

  • Negative plate and lithium ion battery comprising same

    CN113299883A

Cited By

  • Lithium Metal Anode of Sandwich Structure Comprising Metal Meshes Bonded on Both Surfaces, and Method for Manufacturing the Same

    KR103015431B1